Late presentation of an anomalous left coronary artery from the pulmonary artery treated with conservative surgical management with long-term cardiac magnetic resonance imaging follow-up. (23rd February 2017) - Gouda, Pishoy; Gouda, John; Butler, Craig; Welsh, Robert C
Anomalous origin of the left coronary artery from the pulmonary artery is rare congenital abnormality that most commonly presents in childhood and is associated with a high mortality. In the elderly, patients may present acutely with arrhythmias or signs of ischemia or with vague chronic presentations of shortness of breath and fatigue. In the high-risk elderly population, it is unclear as to whether conservative surgical management by means of suture ligation of the left coronary artery is associated with positive long-term outcomes. We present a case of a 69-year-old patient diagnosed with anomalous origin of the left coronary artery from the pulmonary artery, which was treated with conservative surgical management and followed up for 15 years with cardiovascular magnetic resonance imaging, with positive outcomes.